The Effectiveness of Gamification on Academic Achievement in Biology Among Senior Secondary Students - Josephine Ese Konyeme; Rita Ewere Chukwuka (Indonesian Journal of Innovative Teaching and Learning, 2025)
Background: This study examines the effectiveness of gamification in improving biology achievement among senior secondary students in Delta State, Nigeria, where context-specific evidence is still limited. Objective: To evaluate the impact of gamification on academic performance, motivation, engagement, and knowledge retention. Method: A quasi-experimental design involved 80 students from four schools, divided into an experimental group (n=40) receiving gamified biology lessons and a control group (n=40) taught with traditional methods; data were collected via pre- and post-tests, motivation and engagement questionnaires, a delayed retention test administered several weeks after the intervention, and observational checklists. Result: The experimental group significantly outperformed the control group on the post-test and showed higher motivation, engagement, and retention of biological concepts. Conclusion: Gamification effectively enhances this level's learning experiences and academic outcomes in biology. Contribution: The study provides context-specific evidence from Delta State that supports integrating high-tech and low-tech gamification into the curriculum alongside teacher training, particularly in resource-limited settings.